2017
DOI: 10.1093/jac/dkx302
|View full text |Cite
|
Sign up to set email alerts
|

Optimal cure rate by personalized HCV regimens in real-life: a proof-of-concept study

Abstract: Even with newer DAA regimens, an integrated interpretation of clinical and virological pretreatment parameters, including natural RASs, may play a relevant role in bringing SVR rates close to the highest achievable. Treatment tailoring can be foreseen in 'hard-to-treat' patients, but also in 'easy' patients with favourable indicators, whereby a simplification/shortening of recommended regimens can be indicated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 10 publications
0
9
0
Order By: Relevance
“…The presence of substitutions conferring resistance to NS5A inhibitors has been widely reported both in therapy-naïve and in relapser patients from Europe [ 10 , 33 , 35 38 ], USA [ 37 , 39 , 40 ], and Asia [ 41 43 ]. However, NS5A sequences from South America are poorly analyzed yet [ 9 , 44 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The presence of substitutions conferring resistance to NS5A inhibitors has been widely reported both in therapy-naïve and in relapser patients from Europe [ 10 , 33 , 35 38 ], USA [ 37 , 39 , 40 ], and Asia [ 41 43 ]. However, NS5A sequences from South America are poorly analyzed yet [ 9 , 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…The presence of baseline NS5A RASs impacts treatment outcome in some patient groups by affecting SVR rates. The detection of NS5A preexistent RASs may play a relevant role in the choice of first-line treatment regimens or in the simplification/shortening of recommended regimens, in order to bring SVR rates close to the highest achievable [ 27 , 38 , 41 , 53 ], in particular in countries such as Uruguay, where only two different DAA-containing treatment regimens are approved for their use.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, a real-life study reported how 130 DAA naïve HCV-infected patients who received baseline RASs guided therapy achieved 100% of SVR12 9 . The authors concluded that this strategy could help to minimize or eliminate relapses.…”
Section: Discussionmentioning
confidence: 99%
“…Cento et al . 9 reported 100% sustained virological response (SVR) rate in DAA-naïve patients undergoing treatment guided by baseline RASs in clinical practice. Nonetheless, they did not compare with a control population without RAS-guided treatment.…”
Section: Introductionmentioning
confidence: 99%
“…Even with newer DAAs, for instance, patients with GT3 infection and natural RASs may more frequently experience virological failure 13 , 14 . Under these conditions, a tailored approach in some (not infrequent, though) real-life situations may help in bringing the cure rate closer to the 98–99% 5 , 9 , 11 , 15 .…”
Section: Introductionmentioning
confidence: 99%